2009
DOI: 10.1108/14777260910979326
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment – a touchy subject for nurses

Abstract: This paper illustrates the prevalence of different types of SH and the causes for male and female nurses that have not been investigated previously. The results help health managers make informed decisions in regard to intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 35 publications
8
54
4
Order By: Relevance
“…For the studies focused on nurses, some of them reported that physicians or other coworkers were identified as the primary perpetrators of SH 7,18,29) . Other literature demonstrated that the most common perpetrators in all types of SH were patients, followed by doctors or other staff 12,25) . The prevalence of SH by patients' relatives was reported to be lower than the prevalences of SH by colleagues and patients 7,18) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the studies focused on nurses, some of them reported that physicians or other coworkers were identified as the primary perpetrators of SH 7,18,29) . Other literature demonstrated that the most common perpetrators in all types of SH were patients, followed by doctors or other staff 12,25) . The prevalence of SH by patients' relatives was reported to be lower than the prevalences of SH by colleagues and patients 7,18) .…”
Section: Discussionmentioning
confidence: 99%
“…As to the issue of the perpetrators of SH, physicians and other coworkers have been reported as the most common source of SH 4,18) . Some literature has also demonstrated that the most common perpetrators of all types of SH were patients, followed by doctors, other work colleagues and visitors or patients' relatives 12,19) . A broad type of behaviors can be viewed as SH.…”
Section: Department Of Psychiatry Chang Gung Memorialmentioning
confidence: 99%
See 1 more Smart Citation
“…The pilot was distributed to 20 participants and the feedback was used to make slight modifications and ultimately tailor it to the target population. The threshold on whether harassment was deemed serious was set at the values specified in the study by Cogin, J. et al (2002); when at least 60% of female staff and 34% of male staff report sexual harassment [8]. Of the 500 questionnaires, 233 were returned.…”
Section: Methodsmentioning
confidence: 99%
“…23 Empirically, nurses are the most vulnerable population to SH among hospital workers. 24,25 Numerous studies have reported a high prevalence of SH among nurses during their careers, ranging from 30 to 97% . For female doctors, SH has also been commonly reported to be as high as 77% among family physicians, 58.3% among residents and 59% among medical students.…”
Section: Broad Types Of Sexual Harassment (Sh)mentioning
confidence: 99%